Análises da produtividade da água com imagens landsat 8 no perímetro de irrigação nilo coelho - Teixeira, Antônio Heriberto De Castro; Leivas, Janice Freitas; Andrade, Ricardo Guimarães; Hernandez, Fernando Braz Tangerino [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
The Nilo Coelho (NC) irrigation scheme, located in the Brazilian semi-arid region, is an important irrigated agricultural area. Land use change effects on actual evapotranspiration (ET), biomass production (BIO) and water productivity (WP) were quantified with Landsat 8 images and weather data in this scheme covering different thermohydrological conditions. The SAFER algorithm was used for ET acquirements while the Monteith's radiation model was applied to retrieve BIO. For classifying irrigated crops and natural vegetation, the SUREAL model was used with a satellite image representing the driest period of the year. The average values for ET, BIO and WP in irrigated crops, ranged, respectively, from 1.6 ± 1.9 to 4.2 ± 1.9 mm day-1; 59 ± 86 to 146 ± 91 kg ha-1 day-1; and 2.0 ± 1.5 to 3.0 ± 1.2 kg m-3. The corresponding ranges for natural vegetation (Caatinga) were from 1.2 ± 1.8 to 2.6 ± 1.8 mm day-1; 43 ± 78 to 76 ± 78 kg ha-1 day-1; and 1.6 ± 1.4 to 2.7 ± 1.1 kg m-3. The incremental values, which represent the effects of the replacement of natural vegetation by irrigated crops, were 40, 54 e 23%, for ET, BIO e WP, respectively.
Water productivity assessments with landsat 8 images in the nilo coelho irrigation scheme
Keywords: Biomass production; Evapotranspiration; Land use change